Integrating Psychology, Public Health, and Multidisciplinary Medical Sciences for Holistic Care - Fawaz Adeem Alharthi; Hussain Ali A. Alghamdi; Mohammed Hamed S. Alghamdi; Abdulrahman Hamed S. Alghamdi; Raji Ali M. Omdah; Turki Romaih Alromaih; Abdulaziz Hamad O Alshalan; Abdullah Mohammed A Alaskar; Abdulslam Zaid A. Alfayez; Abdulmajeed Abdullah Albariqi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Integrating diverse medical specialties, including psychology, public health, medical technology, laboratory sciences, and multidisciplinary medical specialties, is paramount in enhancing overall care and patient care and overall outcomes. Integrative care models, including integration of psychological care in routine care, have proven effective in care and mental management through enhanced effectiveness and reduced mental care-related stigma. Besides, medical technological and laboratory diagnostics, including point-of-care testing and molecular diagnostics, enable effective and timely diagnoses, opening doors for personalized care. Besides, care integration models, including Patient-Centered Medical Home (PCMH), prioritize collaboration between medical professionals in managing disease, opening doors for overall care and patient satisfaction. In conclusion, reiterating in this article, multidisciplinary collaboration in healthcare plays a significant role in enhancing overall care and overall outcomes for a patient, and closing gaps in accessing care.